Physical Activity in Cardiovascular Disease Prevention: A Narrative Review - Oćwieja, Zuzanna; Wyborska, Agata; Fengler, Karolina; Jakubowska, Olga; Pietrzak, Kamila; Gascon Carreno, Marcel; Urbanik, Agata; Mińkowski, Mikołaj; Kominiak, Dominika; Solecka, Katarzyna (Quality in Sport, 2026)
Background. Cardiovascular disease (CVD) remains the leading global cause of death and a major source of disability despite advances in pharmacological and interventional care. Since a substantial part of the remaining burden is still related to modifiable behaviors, physical activity continues to play a central role in prevention. Aim. To summarize current evidence on physical activity as a non-pharmacological intervention in the primary and secondary prevention of CVD, with particular attention to dose-response relationships, sedentary behavior, major cardiometabolic risk factors and exercise-based cardiac rehabilitation. Material and methods. This narrative review used the uploaded outline as the organizing framework. PubMed and major society sources were searched for English-language publications from January 2018 to March 2026 using combinations of terms related to physical activity, cardiovascular prevention and sedentary behavior. International guidelines and scientific statements were prioritized. Results. Higher physical activity levels are consistently associated with lower all-cause and cardiovascular mortality, with the largest relative gains usually seen when people move from inactivity to modest activity. Device-based studies make this message easier to translate into practice through step counts and habitual movement patterns, while also showing that sedentary time is an in dependent cardiovascular risk exposure. Physical activity favorably affects endothelial function, inflammation, insulin sensitivity, adiposity, blood pressure, and lipid metabolism. In secondary prevention, exercise-based cardiac rehabilitation improves health-related quality of life and reduces hospital admissions, and telehealth-supported models can widen access for selected patients. Conclusions. Physical activity is key in cardiovascular prevention. Patients should be helped to move more, sit less, interrupt prolonged sitting, and maintain realistic activity patterns over time.